Analisis Kepuasan Pelanggan terhadap Pelayanan di Toko Diario Cabang Banjarmasin - Putrie Zahra Aprillia; Abdurrahim Abdurrahim; Junaidi Junaidi (Jurnal Manajemen Riset Inovasi, 2025)
: This study aims to determine: (1) To determine and analyze the quality of service of the Diario Shop Banjarmasin Branch (2) To determine and analyze what things need to be developed and improved at the Diario Shop Banjarmasin Branch so that customer satisfaction increases.This research employs a qualitative survey approach, collecting primary data through interviews, observations, and documentation. However, the implementation of activities so far has been deemed not fully aligned with the expected objectives. Therefore, to ensure the smooth progress of the work, improvements need to be made. The quality of service carried out by Toko Diario Banjarmasin Branch, in order to increase customer satisfaction and increase sales turnover which is still not stable, but has progressed from month to month. The results of this study indicate: (1) Diario Shop Banjarmasin Branch meets customer satisfaction with timeliness, accuracy of service quality, courtesy, friendliness, and comfort. Diario Stores have carried out service quality in accordance with good service criteria. (2) We recommend that Toko Diario needs to develop more facilities and make several upgrades to its sales in order to improve service quality by providing clear and detailed product information to increase customer satisfaction.